Improving the benefits and cost of using emerging technologies for sustainable recovery from COVID-19 in manufacturing industries - Nur, S. M. Shafaat Akhter; Salman, Sheak; Habib, A. K. M. Ahasun; Ali, Syed Mithun; AlArjani, Ali; Taqi, Hasin Md. Muhtasim (Frontiers in Environmental Science, 2022)
The ongoing COVID-19 pandemic has manifold disastrous effect on different service and production sectors, and manufacturing industries are no exception. Emerging technologies (ETs) can play a pivotal role in reviving these ailing manufacturing industries. However, the cost of implementing and operating ETs is a prime concern. Nonetheless, the important attributes that will minimize the cost and harness the advantages of the technology are still to be explored. To address this gap, this research seeks to examine the critical attributes required for the effective and efficient deployment of ETs. At first, a detailed literature review was conducted to identify and sort the attributes influencing the effective use of ETs in manufacturing industries. After that, Fuzzy-TODIM (Portuguese abbreviation of “Interactive and Multi-Criteria Decision Making”) method was used to rate the importance of the attributes. The result reveals that, “Inventory and Resource Management” tops the attribute list responsible for exploiting the optimal usage ETs, followed by “Development of Skilled Workforce” and “Supplier and Service Management Capability,” respectively. This paper will assist industry professionals not only in using ETs but also getting the best yield from them strategically and practically.